Magnetic properties of rare-earth zigzag chain systems RAgSe2 (R = Ho, Er, Tm, and Yb). Issue 1 (1st March 2022) - Mizutami, S.; Ohmagari, Y.; Onimaru, T.; Shimura, Y.; Yamamoto, R.; Umeo, K.; Takabatake, T.
Abstract: In an antiferromagnetic zigzag chain, competition between the nearest and next-nearest neighbor interactions could give rise to magnetic frustration. Magnetic semiconductors R AgSe2 ( R = Ho, Er, Tm, and Yb) crystallize in the ErAgSe2 -type orthorhombic structure, where the R ions form a zigzag chain along the orthorhombic a-axis. The magnetic susceptibility data for all the samples follow the Curie-Weiss law between 40 and 300 K. The values of the effective magnetic moment μ β α are close to those expected for the free R 3 + ions. Negative values of the paramagnetic Curie temperature θρ indicate antiferromagnetic interactions. For R = Ho and Tm, the specific heat C(T) data exhibit no anomaly down to 0.4 K, which is ascribed to the nonmagnetic singlet ground states under the crystalline electric fields. On the other hand, for R = Er, C ( T ) shows peaks at T 1 = 1.3 K and T2 = 0.9 K, indicating successive antiferromagnetic transitions. For R = Yb, C ( T ) shows a lambda-type anomaly at T m = 1.8 K. The magnetic entropy at T m is only 30% of R ln2 expected for the ground state doublet, suggesting magnetic fluctuations above T m .